Argilliturbation and Site Formation Processes in East Africa : the case of Nadung’a 4, West-Turkana. - (:unkn) unknown (My University, 2005)
East African Plio-Pleistocene deposits contains archaeological sites from fluvio-lacustre environments. A number of works allow us to discuss the modifications of assemblages recovered from fluvial channel or banks. In contrast, sites retrieved from foodplain deposits are generally assumed to be well preserved and few studies have adressed site formation processes in such environments. The site of Nadung's 4 has yielded detailled data conerning typical modifications in this environnement.
Keywords: African Research